Efficacy of a Persian Herbal Remedy and Electroacupuncture on Metabolic Profiles and Anthropometric Parameters in Women with Polycystic Ovary Syndrome: A Randomized Controlled Trial: - Rouhani, Maryam; Motavasselian, Malihe; Taghipoor, Ali; Layegh, Parvaneh; Asili, Javad; Hamedi, Shokouh Sadat; Badiee Avval, Shapour (Galen Medical Journal, 2019)
Background: The most prevalent endocrine disorder in women of reproductive age is polycystic ovary syndrome (PCOS). The purpose of this study was to evaluate the efficaciousness of a Persian herbal remedy, as well as electroacupuncture and the combination of them on metabolic profiles and anthropometric parameters in these patients. Materials and Methods: Eighty overweight women with PCOS were randomly divided into four groups. All of them received metformin 1000 mg and the second group received 5 g of herbal medicine per day (main components: Foeniculum vulgare, Urtica dioica, and Daucus carota), the third group were subjected to 20 electroacupuncture sessions, and the fourth group received both therapies. Results: After 12 weeks, the body fat and body mass index decreased the most in the herbal medicine+electroacupuncture group, and waist to hip ratio decreased the most in the electroacupuncture group. A significant decrease was also observed in fasting insulin, homeostasis model assessment of insulin resistance. A significant increase was seen in the quantitative insulin sensitivity check index in all intervention groups, but there was no noteworthy difference in these parameters in the control group. Total cholesterol and low-density lipoprotein cholesterol decreased significantly in the electroacupuncture groups and herbal medicine+electroacupuncture. Also, a significant decrease was observed in triglycerides, aspartate aminotransferase, and alanine aminotransferase in the herbal medicine groups and herbal medicine+electroacupuncture. Conclusion: It is advisable to use this herbal remedy and electroacupuncture for better treatment of metabolic complications and overweight problems in these patients.Â  [GMJ.2019;8:e1389]Â 